"[H]is Castle was her Proper Habitation": Homes and Dwelling Places in Sarah Fielding's The History of the Countess of Dellwyn (1759). Issue 2 (4th March 2023) - Skinner, Gillian M.
ABSTRACT: Sarah Fielding's The Countess of Dellwyn tells Charlotte Lucum's story. Seventeen, beautiful, raised in rural seclusion, her father manipulates her into marrying sixty-five year old Lord Dellwyn, a decrepit, gout-ridden and wealthy peer whose political influence Mr. Lucum hopes to secure in order to revive his own career. Eschewing the potential for the sentimental approach more obvious in some of Fielding's other work and in near-contemporary novels such as Frances Sheridan's Memoirs of Miss Sidney Bidulph (1761) and others, the narrative voice of The Countess of Dellwyn maintains a distinctly critical distance from its heroine, remorselessly identifying her manifold errors in choices and conduct and resisting casting her as a victim, despite the parts played in her story by both her father and Lord Dellwyn himself. Key to the Countess's downfall is her seduction by fashionable society, a seduction whose effects become most evident when the recently-married couple retire to Lord Dellwyn's country seat at the London season's end. In discussing the use to which the narrative puts Lord Dellwyn's "noble ancient Castle, " swiftly and fashionably redecorated by the young Countess, this article considers how the novel employs houses as a counterpoint to the prevailing critique of its young heroine.